Peran Subdit Gakkum Ditpolairud Polda Bali Dalam Penegakan Hukum Terhadap Tindak Pidana Yang Terjadi Di Wilayah Perairan Polda Bali - I Kadek P. Nova Saskara Widiarta; Ni Komang Sutrisni (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
Bali's waters have strategic characteristics, characterized by the high intensity of shipping activities, marine tourism, and the utilization of marine resources. The Law Enforcement Sub Directorate (Subdit Gakkum) of the Bali Regional Police's Water Police Directorate plays a crucial role as an implementing element of the police function in law enforcement in the waters. This study aims to analyze the role of the Gakkum Sub-Directorate in enforcing criminal acts in the Bali Regional Police's waters and identify factors that influence the implementation of law enforcement. This study uses an empirical legal method with an empirical juridical approach through literature studies of laws and regulations and interviews. The results show that the Gakkum Sub-Directorate has a strategic role in law enforcement against criminal acts in the waters, which is realized through the implementation of investigations, inquiries, prosecutions, security and management of evidence, and the transfer of cases in accordance with the provisions of laws and regulations. However, the implementation of law enforcement in the waters is influenced by various factors, such as geographical characteristics and maritime activities, the availability and quality of human resources, the level of legal awareness of the maritime community, technological developments and maritime crime modes, and the availability of operational facilities and infrastructure.